Mechanical properties of black sugar palm fiber-reinforced concrete - Ferdiansyah, T.; Razak, H.A. (2011)
This article reports the results of an investigation on the engineering properties of concrete containing black sugar palm fiber. Three fiber lengths of 15, 25, and 35 mm in four volume fractions, namely 0.2, 0.4, 0.6, and 0.8, were utilized in this investigation. The values of compressive, flexural, toughness, first crack deflection, first crack toughness, and toughness indices are reported for ages up to 90 days. It was observed that the addition of palm fibers slightly increased the flexural strength of concrete. The incorporation of the fibers had no significant effect on the compressive strength. The mix with 0.8 volume fraction and 35 mm length fiber gave higher toughness and ductility compared to other mixes. Â© The Author(s) 2011.